2023
DOI: 10.1038/s41598-023-33395-6
|View full text |Cite
|
Sign up to set email alerts
|

Phobia-specific patterns of cognitive emotion regulation strategies

Abstract: Although fear plays a vital role in survival, an overly active threat detection system could be maladaptive due to its negative health consequences. Putatively maladaptive emotion regulation (ER) strategies are a core problem in phobias. In contrast, adaptive ER strategies could help downregulate the emotion elicited by a threatening stimulus and decrease anxiety. Yet, the number of studies directly examining the pattern of ER strategies linked to various phobias is still scarce. Thus, this study sought to map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Cognitive reappraisal, rather than expressive suppression, is associated with increased positive well-being outcomes and better interpersonal functioning 19 . Adaptive strategies of cognitive emotion regulation are negatively associated with fears and social anxiety 20 . Past studies also found that expressive suppression plays a role in the development and maintenance of psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive reappraisal, rather than expressive suppression, is associated with increased positive well-being outcomes and better interpersonal functioning 19 . Adaptive strategies of cognitive emotion regulation are negatively associated with fears and social anxiety 20 . Past studies also found that expressive suppression plays a role in the development and maintenance of psychopathology.…”
Section: Introductionmentioning
confidence: 99%